Biological education and community development - A Caribbean perspective - King, Winston K. (Taylor and Francis, 1980)
This article identifies six trends influencing the biology curriculum in the Caribbean. They are: 1) the search for more and better food sources, 2) the shift towards family planning, 3) the focus on disease prevention and control, 4) growing emphasis on environmental education, 5) the need for Caribbean peoples to understand racial differences, and 6) the demystification of mental illness. Two constraints to the role of biological education in community development are external examination syllabuses and a strange notion of what community development entails
Keywords: Biology education